Systematic Literature Review: Tren dan Tantangan dalam Penggunaan Media Pembelajaran Digital untuk Pendidikan Matematika - Marian, Fungky; Handayani, Ruri; Yansyah, Medi (Circle: Jurnal Pendidikan Matematika, 2025)
This study aims to examine the development and challenges in the use of digital learning media in mathematics education through a Systematic Literature Review (SLR) approach. The research method is qualitative, with data obtained from the Scopus database, which is then analyzed using Vosviewer software to visualize relationships between keywords, research trends, as well as collaborations among authors and institutions. The findings reveal that digital media, such as games and interactive applications, have improved students' understanding of mathematical concepts, particularly in geometry, which requires a visual approach. Additionally, these media have contributed to the development of students' computational thinking skills. However, there are significant challenges, including limited access to technology, geographical disparities, and difficulties in integrating digital media into local educational curricula. This study is limited to literature sourced exclusively from the Scopus database, potentially overlooking research from certain regions or in languages other than English. For future research, it is recommended to focus on the development of digital learning media tailored to local needs, exploration of artificial intelligence-based technologies, and evaluation of the long-term impacts of their use on learning outcomes. Moreover, international collaboration should be enhanced to expand the accessibility and relevance of digital learning media globally.